Expectation and degrees of freedom for sample variance. (22nd March 2020) - Liu, Xiaofeng Steven; Shin, Hyejo Hailey
Abstract: Computer simulation can be used to demonstrate why the unbiased sample variance uses degrees of freedom ( n −1). This is first demonstrated for sampling from a normal random variable, and in additional simulations for some selected non‐normal random variables, namely, chi‐square and binomial.